Budget Performance Analysis State Treasury Service Office In The Kalimantan Region: Data Envelopment Analysis Approach - Mohammad Arief Barata; Roosemarina Anggraini Rambe; M. Armelly (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the budget performance efficiency of 21 State Treasury Service Offices (KPPN) in the Kalimantan Region for the 2023-2024 period using the Data Envelopment Analysis (DEA) method with the Variable Returns to Scale (VRS) approach. Input variables include operational expenditures, the number of technical employees, and supporting employees, while output variables include the percentage of SPM processed into SP2D, the IKPA value of BUN Authorization, the timeliness of TKD document submission, and the number of HAI-CSO services. The results show that not all KPPNs achieve full efficiency, with the input-oriented approach indicating potential resource savings, while the output-oriented approach emphasizes improving service quality. KPPNs in Pangkalan Bun, Pelaihari, Palangkaraya, and Tanjung Redep are consistently efficient across both approaches. These findings underscore the importance of proportional human resource redistribution, operational budget optimization, and strengthening performance-based monitoring systems to improve the efficiency of treasury services in Kalimantan.